Qualität und Güte im gemeinsamen Forschen mit Menschen mit Lernschwierigkeiten Entwurf und Diskussion von Qualitätskriterien Partizipativer und Inklusiver Forschung - Hauser, Mandy (Verlag Julius Klinkhardt, 2020)
The book deals with the quality of participatory and inclusive research together with people who are considered to have a so-called intellectual disability. Joint research plays an important role in inclusion-sensitive higher education development and has long been demanded and implemented in the context of disability studies under the motto "Nothing about us without us". For the sustainability and impact of the insights gained through these research approaches, addressing the quality of the research work is of central importance. As a basis for this, however, it is first necessary to clarify the question of what actually constitutes scientific quality? Answers to this question will be given, among other things, by referring back to the science-theoretical perspectives of critical theory and feminist research. On the basis of an analysis of topic-specific publications, through interviews with people experienced in research and by discussing specific difficulties and challenges, quality criteria are then developed that highlight the special value of participatory and inclusive research approaches and enable high-quality research.